2022
DOI: 10.1680/jmacr.20.00162
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of autogenous healing in cracked mortars under marine water exposure

Abstract: In this study, autogenous crack healing was quantified in mortar specimens under various exposure conditions. Specimens were cracked at 28 days and then exposed to a single type of environment: submersion in freshwater, submersion in marine water or cyclic submersion in marine water followed by drying daily (tidal conditions). Instead of taking measurements at a few selected points along the crack length, crack widths were innovatively determined through periodic measurements monitoring the entire crack surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Liu et al 39 reported that the crack closure ratio of a 400 μm crack in seawater to be 2.6 times than of the same crack healed in tap water. The Presence of different ions dissolved in seawater, e.g., Mg 2+ , helps with the formation of new healing products such as brucite (Mg(OH) 2 ) that can promote crack healing efficiency of ECC in addition to portlandite (CA(OH) 2 ) and calcite (CaCO 3 ) 26 . These additional healing products can recover the stiffness of a cracked specimen through enhancing the fiber bond.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al 39 reported that the crack closure ratio of a 400 μm crack in seawater to be 2.6 times than of the same crack healed in tap water. The Presence of different ions dissolved in seawater, e.g., Mg 2+ , helps with the formation of new healing products such as brucite (Mg(OH) 2 ) that can promote crack healing efficiency of ECC in addition to portlandite (CA(OH) 2 ) and calcite (CaCO 3 ) 26 . These additional healing products can recover the stiffness of a cracked specimen through enhancing the fiber bond.…”
Section: Results and Analysismentioning
confidence: 99%
“…Although the extend of healed cracks in the presence of the moisture ranges from 50 to 150 μm, the healed crack width for seawater exposure is ranging between 200 and 700 μm. 1,12,25,26 The studies on the self-healing in ECC conclude that natural environment where cycles of moisture are available, plus maintaining the cracks width below 150 μm are favorable conditions for a robust self-healing. 17,19,20 Crystalline admixture (CA) is a market label used to categorize a group of hydrophilic admixtures containing active chemicals that form water-insoluble precipitates upon reaction with water, leading to densification of calcium-silicatehydrates (C-S-H) and resisting water penetration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of self-healing of cracks in elements exposed to water flowing through cracks has also been confirmed [48]. The course of self-healing was also studied in conditions such as seawater action [49,50].…”
Section: Introductionmentioning
confidence: 89%